Human brucellosis in Portugal—Retrospective analysis of suspected clinical cases of infection from 2009 to 2016 - Pelerito, Ana (PLoS One, 2017)
Brucellosis is a zoonosis that is emerging in some regions of the world. Although brucellosis is a disease of obligatory declaration and is not eradicated in Portugal, no prevalence data is available in this country. In this study, we retrospectively analyzed the data available at the Reference Laboratory at the Portuguese National Institute of Health during the past 7 years (2009–2016) in order to get insight into the epidemiological scenario of brucellosis in Portugal. A total of 2313 biological samples from patients with clinical suspicion of brucellosis were subjected to immunological techniques for laboratory diagnosis. From 2010 to 2015, a subset of 259 samples was subjected to molecular methods. According to the available data, 167 out of 2313 (7.2%) samples had positive serology for Brucella spp. and 43 out of 259 samples (16.6%) were positive for B. melitensis by real time PCR, being classified as biovar 1 and 3. This study draws attention to the importance of integrating clinical and laboratory data of human cases in order to increase the efficacy of the response measures in case of outbreaks.